Digital Dilemmas Transforming Gender Identities and Power Relations in Everyday Life - Parry, Diana C.; Johnson, Corey W.; Fullagar, Simone; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The proliferation of digital technologies, virtual spaces, and new forms of engagement raise key questions about the changing nature of gender relations and identities within democratic societies. This book offers a unique collection of chapters that brings together scholars from diverse backgrounds to explore how gender experiences and identities are being transformed by digital technologies in ways that affirm or deny social justice. .
Chapter 1 - Digital Dilemmas: Transforming Gender Identities and Power Relations in Everyday Life -- Section I: Theory in Digital and Leisure Contexts -- Chapter 2 - Laughing at Injustice: #DistractinglySexy and #StayMadAbby as Counternarratives -- Chapter 3 - Digital Black Feminism -- Section II:Methodological Discussions and Guideposts -- Chapter 4 Online Qualitative Methods: Confronting New Possibilities and Challenges Within a Social Justice Perspective -- Chapter 5 - Appnography: Modifying Ethnography for App-Based Culture.-Section III: Dilemmas at the Intersection of Gender, Gender Identity, and Digitality -- Chapter 6 - Writing Recovery from Depression Through a Creative Research Assemblage: Mindshackles, Digital Mental Health, and a Feminist Politics of Self-Care -- Chapter 7 -Playing with Zombie Problems: Exploring the Gender-Digital- Play Assemblage in Online Mental Health Campaigns -- Chapter 8 - The Impact of Digital Culture on Women in Sport -- Chapter 9 - This Girl Can? The Limitations of Digital Do-It-Yourself Empowerment in Women's Active Embodiment Campaigns -- Chapter 10 -Making Gender and Motherhood Through Pedagogies of Digital Health and Fitness Consumption: 'Soon It Made Us More Active as a Family' -- Chapter 11 - Digital Dilemmas Through Networked Assemblages: Reshaping the Gendered Contours of Our Future.
Keywords: Sex; Sports -- Sociological aspects; Digital media; Gender Studies; Sport Sociology; Digital and New Media